Maojok: Akulturasi Ilmu Gramatika Arab di Minangkabau (Studi Kasus Pondok Pesantren Nurul Yaqin, Ringan-Ringan): Urgensi Ilmu Gramatika Arab bagi Pelajar Pesantren di Indonesia - fil amri, Fauzul; Gamasari, Rita; Amin, Irsal (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This research aims to describe the process of acculturation of Arabic grammar in Minangkau using the maojok method. The method used in the research is a qualitative method. Data was obtained by means of interviews, observations and documents. The results of this research show that the maojok method which is an integral part of the learning process at the Nurul Yaqin Islamic Boarding School is a real implementation of the concept of acculturation. Assimilation occurs through combining Arabic language patterns with Minangkabau language in this method. Integration is realized in an effort to maintain local cultural identity while combining elements of Arab culture. Accommodation is seen in joint efforts between teachers and students to create a harmonious learning situation by combining the two cultures. Meanwhile, cultural defense is reflected in the continued use of the maojok method as a cultural heritage of Islamic boarding schools that must be maintained.